Analisis Hubungan Anemia Dalam Kehamilan Dengan Kejadian Bayi Berat Lahir Rendah (BBLR) Di UPT Puskesmas Lawawoi - Hasrul; Hafid, Aslinda; Nurjannah, Nurjannah; Nurbaya, ST; Tahir, Muhammad; Maisyaroh, Meriem (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: One of the efforts in realizing quality human resources is the guarantee of health quality. One of the indicators used to measure the quality of health is infant mortality rate (IMR). LBW is one of the main causes of infant mortality, with 40% of all child deaths occurring during the neonatal period. Cumulatively, about 15.5% of all deliveries are LBW and 95.6% occur in developing countries. (Sari 2021). Anemia that occurs during pregnancy is one of the major problems that occur. The impact caused by anemia in pregnant women is a variety of complications for the mother, in the form of pregnancy disorders, especially in the fetus such as Low Birth Weight Infants (LBW), impaired growth of the baby's organs and brain, and malnutrition or malformations in the baby who is born. (Audrey and Candra 2016) Methods: The research method used is observational research. The research design is descriptive analytic with a cross-sectional study approach. Results: The sampling technique in this study used Non Probability Sampling, namely Purposive Sampling. The number of samples was 47 babies with LBW during 2021.Conclusion: There is a significant relationship between anemia in pregnancy and the incidence of low birth weight (LBW) in the working area of UPT Puskesmas Lawawoi, Sidrap Regency, obtained a p value = 0.001 ˂ 0.05 (α).